Heterometallic 3d-4f MOFs based on a polydentate macrocyclic ligand for photocatalytic CO2 reduction and amine formylation - Yudong Shen; Shuqi Tong; Weile Wang; Bo Li; Shimin Fan; Yunjie Luo; Fanjun Meng; Wei Xu (Chemical Engineering Journal, 2026)

TPGS Modified Phospholipid-free and Cholesterol-free Ethosomes Enhance Chemical Stability and Transdermal Permeation Of Retinol - Fanjun Xu; Meiting Li; Hang Ruan; Teng Guo; Zhi Wang; Nianping Feng; Yongtai Zhang (AAPS PharmSciTech, 2026)

Chitooligosaccharides Improves Severe Acute Pancreatitis by Reducing Intestinal Mucosal Injury and Regulating Intestinal Microbiota - Fanjun Meng; Guangchen Sun; Yan Zhao; Yayuan Luo; Yanou Bai; Weiyan Lyu; Hao Han; Xu Liu (Probiotics and Antimicrobial Proteins, 2026)

Microneedles self-implanting Astragalus polysaccharides-hybridized composite hydrogel combined with minoxidil to enhance in situ anti-androgenetic alopecia - Jiaqi Li; Meng Long; Fanjun Xu; Zulalan Abudureyimu; Jing Li; Teng Guo; Nianping Feng; Yongtai Zhang (Drug Delivery and Translational Research, 2026)

Recent advances of photocatalysts for nitrogen reduction reaction and mechanism behind them: How and why modifications change properties - Jin Feng; Wenxing Xu; Xiaorui Xu; Xinlu Wang; Yan Wang; Fanjun Zhang; Yuanyuan Feng; Yuchen Ma; Dapeng Zhang (Journal of Environmental Chemical Engineering, 2025)

Improving storage stability of dairy emulsions via xanthan gum and carboxymethyl cellulose synergy - Qingyun Xu; Jiaming Li; Fanjun Meng; Yanfang Sun; Xuexian Du; Yingle Wu; Jianguo Yan; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2025)

Efficient synthesis of multifunctional α-Fe2O3 QDs/TS-1 as an artificial nanozyme for simultaneous colorimetric detection and photodegradation of tetracyclines - Fanjun Meng; Kunze Wei; Yanan Li; Le Zhang; Shujun Xu; Xifeng Shi; Bo Tang (Chemical Engineering Journal, 2024)

Char and soot records of the Holocene fire history and its implications for climate-vegetation change and human activities within the Guanzhong Basin, southern Loess Plateau, China - Yuzhu Zhang; Qili Xiao; Yan Zhu; Ninglian Wang; Menglei Wu; Yanfeng Li; Jianxi Li; Dou Chen; Xiaoling Huang; Sikai Wang; Pengpeng Cao; Yao Jin; et al. (Science of The Total Environment, 2024)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Ultrafast Self-propelling directionally water transporting wood via cell wall reshaping for water manipulation - Zhe Qiu; Fanjun Yu; Dan Xu; Zengbin Wang; Junya Huang; Shuo Wang; Yanxiao Yang; Yonggui Wang; Jian Li; Zefang Xiao; Yanjun Xie; Kai Zhang (Chemical Engineering Journal, 2023)

Activated microglia–induced neuroinflammatory cytokines lead to photoreceptor apoptosis in Aβ-injected mice - Jing Wu; Ge Gao; Fanjun Shi; Hai Xie; Qian Yang; Dandan Liu; Sichang Qu; Haifeng Qin; Chaoyang Zhang; Guo-Tong Xu; Fang Liu; Jingfa Zhang (Journal of Molecular Medicine, 2021)

Sensory–sympathetic coupling in superior cervical ganglia after myocardial ischemic injury facilitates sympathoexcitatory action via P2X7 receptor - Jun Liu; Guilin Li; Haiying Peng; Guihua Tu; Fanjun Kong; Shuangmei Liu; Yun Gao; Hong Xu; Shuyi Qiu; Bo Fan; Qicheng Zhu; Shicheng Yu; et al. (Purinergic Signalling, 2013)